2015
DOI: 10.2135/cropsci2015.01.0023
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Changes from a Century of Genetic Improvement of Soybean Cultivars in Northeast China

Abstract: The first soybean [Glycine max (L.) Merr.] breeding program in China was established in the northeast in 1913. A trend analysis of widely grown cultivars across Chinese soybean breeding history may provide a better perspective on the genetic progress in soybean. The objective of the current study was to assess the genetic change of 15 phenological, yield, and agronomic traits on widely grown cultivars in northeast China. Sixty-four soybean cultivars representing a span of 84 yr of release were included. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…Our database, primarily from small‐plot experiments, showed similar yield gain per year to the 25.8 kg ha −1 yr −1 reported by FAO between 1960 and 2014 (FAO, 2017). Historical time trends for soybean yield average increase have been documented in the United States (23 kg ha −1 yr −1 ; Long, 2013; Rowntree et al, 2013; Specht et al, 2014; Wilson et al, 2014), China (11 kg ha −1 yr −1 ; Wu et al, 2015), Argentina (44.33 kg ha −1 yr −1 ; de Felipe et al, 2016), and Brazil (41 kg ha −1 yr −1 ; de Toledo, 1990). Our database indicates that yield improvement was mostly associated with increased biomass and little or no change in HI, in agreement with previous studies (Schapaugh and Wilcox, 1980; Spaeth et al, 1984; Johnson and Major, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Our database, primarily from small‐plot experiments, showed similar yield gain per year to the 25.8 kg ha −1 yr −1 reported by FAO between 1960 and 2014 (FAO, 2017). Historical time trends for soybean yield average increase have been documented in the United States (23 kg ha −1 yr −1 ; Long, 2013; Rowntree et al, 2013; Specht et al, 2014; Wilson et al, 2014), China (11 kg ha −1 yr −1 ; Wu et al, 2015), Argentina (44.33 kg ha −1 yr −1 ; de Felipe et al, 2016), and Brazil (41 kg ha −1 yr −1 ; de Toledo, 1990). Our database indicates that yield improvement was mostly associated with increased biomass and little or no change in HI, in agreement with previous studies (Schapaugh and Wilcox, 1980; Spaeth et al, 1984; Johnson and Major, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies on changing trends in agronomic traits in these widely grown soybean cultivars indicated that, in North East China, newer cultivars had earlier flowering, shorter plants with fewer branches, higher lodging resistance and higher yields per plant than older cultivars, and in the YHH region, modern cultivars had shorter plants, fewer nodes, higher lodging resistance, more seeds per pod and heavier seeds than older cultivars (Wu et al 2015;Wang et al 2016). These results may shed light on strategies for soybean root improvement in different production regions.…”
Section: Suggestions For Root-trait Improvement In Soybean Breedingmentioning
confidence: 97%
“…In the past century through to 2015, more than 2400 soybean cultivars were developed in China (Wang et al 2016). During this time, yield, agronomic and phenological traits of soybean have markedly improved (Zheng et al 2006;Tian et al 2007;Zhao et al 2008Zhao et al , 2012Xu et al 2011;Wang et al 2015;Wu et al 2015;Qin et al 2017). Modern soybean varieties tend to have greater root weight, root volume, root surface and lateral root length than older varieties (Yang et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the genetic basis of yield increase, cultivars released in different years should be sown in a common environment (Specht et al, 1999;De Bruin e Pedersen, 2008;. Such research carried out in several soybean-producing countries has shown plant-specific morphophysiological changes for each site because of yield improvement Yu et al, 2009;Jin et al, 2010;Koester et al, 2016;Wu et al, 2015). The increase of soybean yield in Brazil, carried out through breeding, was not accompanied by researches that could clarify the morphophysiological changes that occurred in the plant, and their contribution to the main objective of breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Modern North American soybean cultivars partition more carbohydrates into grains(Koester et al, 2014). In this context, among the yield components that contributed most to yield increase was the number of grains per plant, both in Chinese(Jin et al, 2010;Wu et al, 2015) and in North American(De Bruin e Pedersen, 2008; cultivars.…”
mentioning
confidence: 99%